Introduction to fixed-income analysis and portfolio management - Fabozzi, Frank J. (London The Mit press, 2024)
A concise but comprehensive introduction to fixed income analysis for undergraduate and graduate students. Offering more concise and less technical coverage of the material featured in the classic text Bond Markets, Analysis, and Strategies, this streamlined book is rightsized for a one-semester fixed-income course. In accessible terms, Frank Fabozzi describes the sectors of the fixed-income market, details how to value fixed-income instruments, and shows how to measure interest rate risk and how to manage a fixed income portfolio.